Visual field defects in the optic disc drusen - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To evaluate the visual field defects in patients with visible and buried optic disc drusen. Material and methods: 40 patients (22 women and 18 men, mean age 49.8 years) with optic disc drusen were studied prospectively for clinical and electrophysiological evidence of impaired optic nerve function. Visual acuity, colour perception, presence of an afferent pupillary defect, visual evoked potentials (VEP), and visual field were analyzed. The visual field defects were classified by their predominant pattern. Statistical analysis was performed using a chi-squared test and the Fisher exact test. Results: The visual field defects were found in 63.2% of eyes with optic disc drusen. The two most common pattern of visual field loss were enlargement of blind spot and nerve fiber bundle defects. 76.3% of eyes with visible optic disc drusen had abnormal visual fields compared with 46.5% of eyes with buried drusen, p=0.011. Results of electrophysiological studies showed abnormal VEPs in 44.7% of eyes with visible drusen an in 20% of eyes with buried drusen, p=0.032. Conclusion: Visual field loss are the most common visual symptoms in the optic disc drusen. Visual field defects in eyes with visible drusen are more frequent than in eyes with buried drusen. Changes in perimetry are strongly associated with visual acuity loss and abnormal VEP